2012
DOI: 10.1108/17506141211236785
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences and applicants' procedural fairness perceptions

Abstract: PurposeThe purpose of this paper is to examine Chinese traditionality as a predictor of applicants' procedural fairness perceptions in selection, and both its direct and indirect relationship with applicants' recommending behavior, job performance and turnover intention three to four months post hire. Traditionality, as a moderator of perceptions‐outcomes relationships, is also tested.Design/methodology/approachSurvey data of 218 supervisor‐subordinate dyads were collected from Mainland Chinese organizations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…fair treatment, openness, two-way communication) aspects. Our interest in procedural fairness per se is that, in addition to the outcomes noted above, it associates positively with employee job performance (Wang et al , 2012), including 18 months post-hire (Konradt et al , 2017). As such, it is of practical value to understand the antecedents of these perceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…fair treatment, openness, two-way communication) aspects. Our interest in procedural fairness per se is that, in addition to the outcomes noted above, it associates positively with employee job performance (Wang et al , 2012), including 18 months post-hire (Konradt et al , 2017). As such, it is of practical value to understand the antecedents of these perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the total number of studies involved is small, and most notably, there has yet to be a study in which the characteristics we referenced have been examined together for their impact on both applicants’ expectations, and their experience of procedural fairness, in an employee selection process. For example, although there are investigations of procedural fairness perceptions in selection contexts that incorporate Confucianism (Wang et al , 2012), personality (Truxillo et al , 2006) or test-taking experience (Ryan et al , 1996), no single study examines all three. Analogously, two studies have investigated the impact of procedural fairness expectations on experienced procedural fairness (Bell et al , 2006; Konradt et al , 2017), but neither of them incorporated applicants’ cultural values personality or test-taking experience as antecedents.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, they are likely to obtain good evaluation of their work performance. Previous research has also found that Chinese traditionality was positively associated with employees' job performance (Hui et al, 2007;Wang et al, 2012). We thus put forward the following hypothesis: H3.…”
Section: Hypotheses Developmentmentioning
confidence: 87%
“…It was discovered that studies were conducted in various parts of the world such as in United States (Ahuja, Chudoba, Kacmar, McKnight, & George, 2007;Buttner, Lowe, & Billings-Harris, 2010;Byrne, 2005;Campbell, Perry, Jr, Allen, & Griffeth, 2013;Cantor, Macdonald, & Crum, 2011;Cole, Bernerth, Walter, & Holt, 2010;Coniglio, 2013;Soltis, Agneessens, Sasovova, & Labianca, 2013), China (Lin, 2015;Loi, Hang-Yue, & Foley, 2006;Ma, Liu, & Liu, 2014;Ngo, Loi, Foley, Zheng, & Zhang, 2013;Wang, Hackett, Cui, & Zhang, 2012), Korea (Campbell, Im, & Jeong, 2014;Kim, Solomon, & Jang, 2012;Lee, Kim, & Kim, 2016;Son, Kim, & Kim, 2014), Canada (Chawla & Kelloway, 2004;Flint et al, 2013;Paré & Tremblay, 2007;Tremblay, 2010), Pakistan (Bakri & Ali, 2015;Khan, Abbas, Gul, & Raja, 2015;Shahzad, 2016), India (Aryee, Budhwar, & Chen, 2002;Biswas, 2015;Chalil & Prasad, 2014), Malaysia (Ansari, Hung, & Aafaqi, 2007;Ponnu & Chuah, 2010;Poon, 2012) Singapore (Aryee & Chay, 2001;Ho, 2012), Spain (Silla, Gracia, Mañas, & Peiró, 2010), Indonesia (Zagladi, Hadiwidjojo, & Rahayu, 2015), United Arab Emirates (UAE) (Al Afari & Elanain, 2014), Israel (Meisler, 2013), Australia …”
Section: Location and Settingmentioning
confidence: 99%